建構離島特殊教育支持系統之研究 Constructing Special Education Support Systems in Outlying Taiwanese Islands - 柯惠菁 Hui-Ching Ko; 胡心慈Shin-Tzu Hu; 鄭聖敏 Sheng-Min Cheng (National Taiwan Normal University, 2023)
偏鄉教育資源不足，影響學生學習，一直是政府及許多研究者關心的議題；且雖知離島的特殊教育（簡稱特教）是弱勢中的弱勢，然究應如何支持，卻是文獻及實務長久以來的缺口。本研究探討北部某一研究機構因大學社會責任（University Social Responsibility, USR）專案，而在平安、喜樂（化名）兩島建構特教支持系統之歷程。研究小組透過參與式觀察、訪 談及文件分析，瞭解方案推動小組如何工作，發現專案團隊有別於傳統偏鄉教育僅提供補救與補助的方式，而採取生態觀的社區營造，從盤點現況開始，慢慢在地扎根，再以不斷循環的「示範」、「擾動」策略，進行人員「增能」及資源「連結」，並持續精進發展成長到精緻化，為這個社區架構以學生為中心，由內而外分別包括微觀系統、中間系統、外部系統到鉅觀系統的支持系統。除完成在地接手之任務，還在4年努力下，使兩縣由原先在全國縣市特教評鑑中敬陪末座的乙等和丙等，進步到都是甲等。各生態系統層次中各相關人員也因增能而自我發展，更具自我效能。 Background The lack of adequate educational resources in remote areas has long been a concern of the Taiwanese government. The provision of special education in Taiwan's outlying islands is particularly low. Few studies have investigated the effectiveness of special education in remote areas. The present study explored how special education in the outlying islands of Taiwan can be supported from an ecological perspective, further enhancing our understanding of special education in remote areas. Literature Review Inconvenient transportation and inadequate educational, cultural, and social services in rural areas pose challenges to special education and result in inequality in educational opportunities (Yeh & Sheu, 2021). This inequality is further exacerbated by various structural issues, such as uneven resource distribution and teacher structure as well as low cultural capital, social capital, and student learning motivation (Huang, 2019). The outlying islands of Taiwan lack sufficient resources for providing effective special education; however, providing excessive funding and subsidies for welfare facilities may actually hinder students' growth and overlook shortcomings related to peer stimulation and learning motivation (Ho, 2017; Wang, 2018). Therefore, to provide effective special education services, the issue of remoteness must be considered from the community's perspective and with an understanding of local ecological support systems. This can be achieved by the formation of interdisciplinary professional teams (Cheng & Jhang, 2020; Lai & Liao, 2006; Liao et al., 2006). The key approach is to engage with the community directly to promote its support system. This involves building relationships with community members, providing guidance and training, and encouraging community members to take initiative. This approach also requires the effective use and coordination of resources to integrate support for special education (Hu, 2021; Lee, 2019; Shieh et al., 2012; Wang, 2018). Methods This qualitative study explored how the support network was established through empowerment at the local special education resource center. The research team collected data through observations and interviews and constructed an accurate description of the support system. This study was conducted in two counties in Taiwan, referred to as "Peace" and "Joy" (pseudonyms), by a research institution in northern Taiwan. The project was conducted under the University Social Responsibility initiative. The research was conducted by several individuals in teams. An action team consisted of a professor, a postdoctoral researcher, and resource classroom staff. They had extensive experience in communication and coordination with various professionals and provided indirect services through consultations with teachers and parents. A research team consisted of a professor and two research fellows specializing in disabilities and giftedness. They adopted an objective approach when conducting participatory observations and interviews as well as document analysis. This study included students with and without disabilities, special education teachers, general education teachers, school administrators, professionals, parents, university resource classroom counselors, staff of nongovernmental social welfare organizations, county-level special education administrators, and other county government departments. Data were collected using field notes, interviews, summary sheets, and research journals. The study was conducted from July 2008 to June 2011 and comprised preparation, data collection, and data collation stages. In the preparation stage, the research team participants familiarized themselves with the key aspects of the project and reviewed the literature on rural education. In the data collection stage, the action team contacted local individuals and collected information through observations, recordings, formal interviews, informal conversations, field notes, research diaries, and documents provided by the community or schools. Moreover, the researchers organized and categorized the collected information and engaged in discussions to ensure that the collected data were sufficient to effectively address the research questions. Finally, the research findings were detailed in a report. Results At the end of the project, the special education service support systems had been developed and made significant impacts in the two counties. The structure of the special education service support systems in the two counties was student-center, and received support from the microsystem, the mesosystem, the exosystem, the macrosystem, and the chronosystem. The whole system was turned inside out. Members of each ecosystem empowered themselves through self-improvement. Therefore, confidence among the special education staff in both counties had increased. Students and parents had learned how to self-advocate and generate ideas. From the ecological perspective, the researcher found that the "empowerment" was the core of action in the support system, thus people in the system were able to strengthen their own knowledge, extend the connections to more resources, and furthermore to promote more development in services and support within microsystem, the mesosystem, the exosystem, the macrosystem, and even the interactions between systems. As a result, the public would have the positive understanding on individuals with disabilities, and increase their acceptance and support. Time is an important boost for the two entire outlying island special education support systems to take root, grow, and refine locally, allowing two support systems to be constructed and developed stably. Discussion and Suggestions The researcher discovered a shift in the perspectives in both counties from conservative and isolated mindsets to active engagement and willingness to cooperate with others. Specifically, the process of establishing special education support systems in the outlying islands involved several stages: visiting sites to determine the available resources, gradually becoming familiar with the local culture, initiating start-up activities, and finally connecting resources and completing on-site integrations. This reconstructed support system focuses on students with disabilities and has ecosystem-level features (Shelton, 2018, 2021), as follows: 1. The microsystem system in the innermost circle focuses on the empowerment of individuals, parents, and staff to enhance collaboration among them. 2. The mesosystem aims at improving the stability, exchange, and integration of resources. 3. The exosystem expands the resources and connections of social welfare institutions, hospitals, universities, and other organizations. 4. In the macrosystem, the community culture changed from conservative and isolated to acceptance and engagement, with understanding and support for the disabled students after advocacy by college students with disabilities and parent empowerment activities. 5. The chronosystem provides the time needed for the establishment, growth, and refinement of the support systems.